Artificial intelligence dalam Rekrutmen dan Seleksi Karyawan : Manfaat dan Tantangannya - Sewang Sewang; A. Nur Asri Ainun; Misrah Misrah (Lembaga Pengembangan Kinerja Dosen, 2024)
Artificial intelligence (AI) is revolutionizing recruitment by automating candidate screening, interview analysis, and job success prediction. This study evaluates the benefits and challenges of implementing AI in employee selection through case studies and comparative analysis. The results show that AI improves the efficiency and objectivity of selection, but faces obstacles such as algorithmic bias, system transparency, and user resistance. To overcome these challenges, recommended solutions include bias mitigation strategies, integration of AI with human evaluation, and implementation of best practices. This study provides insights for companies and Human Resource (HR) practitioners in optimizing AI for more effective and fair employee selection.